Determination of antimicrobial resistance patterns of Escherichia coli isolates from farm workers in broiler poultry production and assessment of antibiotic resistance awareness levels among poultry farmers in Lusaka, Zambia - Mwansa, Mwaba; Mukuma, Mercy; Mulilo, Esther; Kwenda, Geoffrey; Mainda, Geoffrey; Yamba, Kaunda; Bumbangi, Flavien Nsoni; Muligisa-Muonga, Elizabeth; Phiri, Nelson; Silwamba, Isaac; Muma, John Bwalya (Frontiers in Public Health, 2023)
The challenges posed by antibiotic-resistant pathogens have continued to increase worldwide, particularly in resource-limited countries. Human-livestock interactions are implicated in the complex AMR causal web. A cross-sectional study was conducted in four districts of Lusaka Province, Zambia to determine the antibiotic resistance patterns, ESBL production of E. coli isolated from stool samples of broiler poultry farm workers, and to assess poultry farmers' antibiotic resistance awareness. Sixty-six human stool samples were collected and processed for E. coli isolation, antibiotic resistance testing, and screened for ESBL production. In addition, 80 farmers were assessed for their level of awareness on antibiotic resistance. A total of 58 single E. coli isolates were obtained which showed high (87.9%) resistance to tetracycline, trimethoprim/sulfamethoxazole (48.3%), and ampicillin (46.8%); followed by nalidixic acid (19.0%), ciprofloxacin (12.1%), cefotaxime (8.6%) and chloramphenicol (5.2%). The prevalence of AMR E. coli was 67.2%, and 29.3% were MDR. Two (3.4%) isolates were identified to be ESBL producers, harboring the CTX-M gene. The study results also showed that broiler farmers were aware and knowledgeable of antibiotic resistance, although knowledge about its impact on human health was low. This study demonstrated the presence of resistant and ESBL producing E. coli among poultry farm workers.